Behaviours that challenge in children with intellectual disability: systematic review and meta-analysis of pharmacological and non-pharmacological interventions - Lye, Valerie; Hassiotis, Angela; Timmerman, Amanda; Alqazlan, Sohil; Dimitrova, Elizaveta; Vegh, Borbala; Totsika, Vaso (BJPsych open, 2025)
Behaviours that challenge are highly prevalent in children with an intellectual disability and can be detrimental to their quality of life and opportunities. The systematic review aimed to investigate the effectiveness of current interventions in reducing behaviours that challenge in children with an intellectual disability (≤18 years-old). We searched five databases (PsychINFO, MEDLINE, Embase, Web of Science and CINAHL) on 26 April 2022 and 1 July 2024, and identified 18 randomised controlled trials (1443 participants) eligible for inclusion since 2014 - 11 investigated non-pharmacological and 9 investigated pharmacological interventions. Risk of bias was assessed using the Cochrane Risk of Bias 2 tool. Non-pharmacological interventions (mostly psychosocial) were significantly effective (Hedges' = -0.20; 95% CI [-0.35, -0.05]), whereas pharmacological interventions (including a wide range of drug classes and substances) were not ( = 0.03; 95% CI [-0.17, 0.24]). Studies using the Child Behaviour Checklist reported significant reductions ( = -0.18; 95% CI [-0.34, -0.02]), whereas studies using the Aberrant Behaviour Checklist did not ( = 0.04; 95% CI [-0.16, 0.25]). A random-effects meta-analysis indicated no overall significant reduction in behaviours that challenge ( = -0.12; 95% CI [-0.24, 0.00]). It is important to note that most studies included were conducted in Western countries and had small sample sizes, and findings may be due to the outcome measures used. Findings support current recommendations that non-pharmacological interventions should be first-line treatment for behaviours that challenge in this population. Evidence highlighted the need for better quality, adequately powered randomised controlled trials.